Ivy and the meanstalk - Lairamore, Dawn. (New York : Holiday House, 2011)
Fourteen-year-old Princess Ivy wants nothing more than to have a little fun in the company of her dragon friend, Elridge, but unless she can recover the magical harp snatched by a thieving youth named Jack long ago, her entire kingdom will suffer an unspeakable fate.
School Library Journal, September 2011
Kirkus Review, April 2011
6.9
3-6
3-6
School Library Journal
Keywords: Princesses -- Juvenile fiction; Dragons -- Juvenile fiction; Giants -- Juvenile fiction; Fairy godmothers -- Juvenile fiction; Fairy tales; Princesses -- Fiction; Dragons -- Fiction; Giants -- Fiction; Fairy godmothers -- Fiction; Fairy tales; Princesses -- Fiction; Dragons -- Fiction; Giants -- Fiction; Fairy godmothers -- Fiction; Fairy tales